Human resource management in Chinese multinationals in the United Kingdom: The interplay of institutions, culture, and strategic choice - Khan, Zaheer; Wood, Geoffrey; Tarba, Shlomo Y.; Rao‐Nicholson, Rekha; He, Shaowei (Human Resource Management, 2019)
This is a study of the challenges faced by Chinese expatriate managers and their strategic responses in securing a workable degree of alignment in UK subsidiaries, against a backdrop of competing home‐country and host‐country pressures. Although much of the literature on home‐country and host‐country effects tends to either adopt a culture or an institutional approach, this study highlights the intermeshed nature of the two. In locating cultural dynamics within an institutional firmament, this study juxtaposes the effects of each and draws conclusions as to their intersection. It is founded on in‐depth interviews with home‐country and host‐country managers. The findings suggest, on the one hand, Chinese expatriate managers tended to see local regulations as an obstacle to efficiency, rather than as a means to access context‐specific complementarities. On the other hand, these managers recognized the need to fit in with established locally specific ways of doing things and in securing sufficient staff buy in to sustain operations, and played a key intermediary role between headquarters and subsidiary.